ISOLASI DAN IDENTIFIKASI GLIKOSIDA STEROID DARI DAUN ANDONG (Cordyline terminalis Kunth) - N. W. Bogoriani (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2008)
Isolation and identification of two steroid glicosides have been conducted from Andong leaves (Cordylineterminalis Kunth). The isolate (4,0 mg white amorphous solid) was obtained after a series of chromatographicseparations. Identification of the isolate using mass spectrometry with positive electrospray showed MW 868 ascalculated from the ion peaks of m/z 891[M + Na]+, and 869[M + H]+. The ion peaks of isolate at m/z 727[(M +Na) - 164]+, 723[(M + H) - 146]+, 705[(M + H) - 164]+, and 413 [(M + H) - 456]+ of its fragments indicated thepresence of three sugars (two terminal sugars and one central sugar) from methylpentose moeity (each of MW 164)linked to an agyicone. Proton magnetic resonance spectrum of the isolate in pyridine-d5 showed characteristicproton signals for three steroid methyls (two angular methyls and one secondary methyl) at d 1.37 (s), 0.85 (s) and1.06 (d, J = 6 Hz); and one methyl group for C25 at d 0,66 ppm (d, J=6 Hz); an ethylene group at d 5.51 ppm (br d, J= 5.7 Hz); signals of the protons linked to C26 at d 4.13 and 3,49 ppm (each br d, J = 9,3 Hz and 9 Hz), and threeanomeric protons at d 6.43 ppm (br s); 5.56 ppm (br s) and 4.57 ppm (d, J = 7.0 Hz). From the above data it can beassumed that the isolate is a spirostan steroidal glicoside.